Immediate complications of hypoxic-ischemic encephalopathy in term neonates with resistive index as prognostic factor - N., Likitha; N., Channabasavanna; B., Mahendrappa K. (International Journal of Contemporary Pediatrics, 2021)
Background: Hypoxemia, a decreased arterial concentration of oxygen, frequently results in hypoxia, or decreased oxygenation to cells or organs. Hypoxic-ischemic encephalopathy (HIE) is a leading cause of neonatal brain injury, morbidity, and mortality globally. In the developed world, incidence is estimated at 1-8 per 1,000 live births, and in the developing world, estimates are as high as 26 per 1,000. The objective of the study is use of resistive index as prognostic factor for immediate neonatal outcome by Doppler ultrasound in birth asphyxia. Methods: 50 babies were subjected to neurosonogram between 12-24 hours of life admitted to tertiary care centre. Resistive index (RI) was measured for all enrolled neonates within 24 hours of life using pulse wave Doppler ultrasound. RI was calculated as: , where S=peak systolic velocity and D=end diastolic velocity. RI was measured for all enrolled neonates within 24 hours of life using pulse wave Doppler ultrasound with 3.5 MHz transducer. RI was calculated as: . A RI between 0.56 and 0.90 was considered normal and neonates were classified as having either normal or abnormal RI. Results: The study conducted states that the mean age taken is 17.12 hours with a p value of 0.82 and the cord pH of mean 6.88 with p value of 0.70 which is suggestive of adverse outcomes in birth asphyxiated babies while the resistive index of cerebral arteries and renal arteries is 0.66 with p value of 0.115 which is statistically significant. The lesser the resistive indices the more severe is the adverse outcome. Conclusions: The immediate consequences of HIE like death, seizures, acute kidney injury which are the parameters in my study has a positive co relation with resistive indices of the cerebral arteries and renal arteries measures respectively.